Laboratory investigation of water extraction effects on saltwater wedge displacement - S. Noorabadi; A.H. Nazemi; A.A. Sadraddini; R. Delirhasannia (Global Journal of Environmental Science and Management)
There is a close connection between saltwater intrusion into aquifers and groundwater extraction. Freshwater extraction in coastal aquifers is one of the most important reasons for the saltwater intrusion into these aquifers. Condition of extraction system such as well depth, discharge rate, saltwater concentration and etc. could affect this process widely. Thus, investigating different extraction conditions comprises many management advantages.  In the present study, the effects of freshwater extraction on saltwater interface displacement have been investigated in a laboratory box. Three different well depths (H) were considered with combinations of 3 different extraction rates (Q) and 3 saltwater concentrations (C) for detailed investigation of the effects of these factors variations on saltwater displacement. SEAWAT model has been used to simulate all the scenarios to numerically study of the process. The experimental and numerical results showed that when the C and Q rates were small and the well depth was shallow, the saltwater interface wouldn’t reach the extraction well, so the extracted water remained uncontaminated. When the C and Q rates were increased and the well was deepened, the salinity of the extracted water became higher. When the Q and C rates were high enough, in the shallow well depth, the final concentration of the extracted water was low but a huge part of the porous media was contaminated by the saltwater, furthermore when the well was deepened enough, the final concentration of the extracted water was increased but a small part of the porous media was contaminated by the saltwater. Finally, the results showed that when the Q and H rates were high enough, the extraction well behaved like a barrier and didn’t allow the advancing saltwater wedge toe to be intruded beyond the wells.